Awareness level of general population regarding keratoconus in Aseer region, Southern of Saudi Arabia - Al-Amri, Abdulrahman (J Family Med Prim Care, 2020)
BACKGROUND: Keratoconus (KC) is a non-inflammatory disease occur to the cornea and cause it to be thin and progressively bulge it into a cone shape which result to blurred vision secondary to irregular astigmatism, frequently eyeglass changing and increase the sensitivity to the bright light, occur usually at second decade of life and stops progressive after fourth decade of life. keratoconus is unknown in aetiology but is a multifactorial disease in causes which divided into genetic and environmental factors, the genetic factors as if patient under ethnic with high prevalence and family history with keratoconus or Atopy. AIM: to assess the general population awareness regarding keratoconus in Aseer region, southern of Saudi Arabia. METHODOLOGY: A descriptive cross-sectional approach was used targeting all population in Aseer region. The study was conducted during the period from January 2019 to May 2020. Data were collected using structured questionnaire included person's socio-demographic data, Participants’ Participants’ awareness regarding KC. The questionnaire was uploaded online using social media platforms. RESULTS: The study included 638 participants who completed the study questionnaire with mean age of 36.8 ± 11.1 years. Exact of 331 (51.9%) of the participants were males. University level of education was reported by 424 participants (66.5%). Fifty-nine participants (9.2%) reported that they had keratoconus. CONCLUSIONS & RECOMMENDATIONS: In conclusion, the study revealed that public awareness in Aseer region regarding keratoconus was moderately poor with defect regarding treatment modalities and its consequences.